Fracture Process of Rock Containing a Hole Before and After Reinforcement: Experimental Test and Numerical Simulation - Linhai Zeng; Futian Zhang; Daobing Zhang; Jiahua Zhang; Huadong Yin (Buildings, 2024)
A deeper understanding of the fracture evolution of hole-containing rocks is helpful for predicting the fracture of engineering rock mass. Based on this, uniaxial compression tests and two-dimensional numerical tests were conducted on red sandstone containing three different shapes of holes before and after reinforcement. The mechanical properties, stress field evolution, and AE energy and AE events during the sample fracture process were studied. The conclusions are that: (1) The reinforced specimens exhibited a significant increase in Young’s modulus and strength compared to the unreinforced specimens (containing a semicircular arch hole). (2) The sample always cracks from the loaded axial direction of the hole, presenting as tensile cracks. Subsequently, stress concentration at the corners of the hole results in shear cracks. Finally, the cracks gradually expand and merge with the holes; there are obvious macroscopic cracks and fracture surfaces on the sample surface, which proves that the sample has been fractured. (3) The reinforcement of the hole-containing sandstone can effectively inhibit the expansion of cracks in the rock. (4) When the stress on the specimen is less than its peak stress, the accumulation of the AE energy and AE events in the reinforced sample are greater than those in the unreinforced sample. The specimen experiences more intense compression-induced fracturing and has a stronger load-bearing capacity.